Clinical study of the tolerability of calcium carbonate-casein microcapsules as a dietary supplement in a group of postmenopausal women - Santiago Palacios; Marieta Ramirez; Mariella Lilue (BioExcel Publishing Ltd, 2020)
Background: Calcium is an essential macronutrient; however, currently supplements are often associated with gastrointestinal (GI) adverse events. The authors investigated the tolerability of a new delivery system for calcium supplementation, based on the functionalization of calcium carbonate (CaCO3) particles by casein proteins, in a randomized, prospective, double-blind, active comparator clinical trial. Methods: Around 208 postmenopausal women were enrolled and randomized 1:1:1:1 to one of the four calcium supplements, taken for 30 days: (1) microencapsulated CaCO3 (microCaCO3) with a 90:10 mineral to protein ratio; (2) microCaCO3 with a 95:5 mineral to protein ratio; (3) conventional CaCO3 tablets; and (4) calcium citrate tablets (CaCitr). The Gastrointestinal Symptom Rating Scale (GSRS) questionnaire was used to evaluate the GI tolerability and the Treatment Satisfaction Questionnaire for Medication (TSQM) to analyze the satisfaction of the participants with the use of the calcium supplements. Results: The mean GSRS scores at baseline differed among the groups from 3.95 to 5.35 without statistical significance. After 1 month use of supplements, the group given microCaCO3 with a 90:10 mineral to protein ratio, showed the lowest mean GSRS score (6.07), while the group given conventional CaCO3 showed the highest score (11.86). According to the completed TSQM questionnaire, the use of supplements was easier for both microCaCO3 groups in comparison with conventional supplements. Conclusions: The microCaCO3 supplement has shown promising results in the context of GI tolerability and patient satisfaction in the use of supplements compared to conventional calcium supplements. The reduction of GI adverse events may increase the compliance to calcium supplements especially important among groups at risk of calcium deficiency.